Periodontal results of different therapeutic approaches (open vs. closed technique) and timing evaluation (< 2 year vs. > 2 year) of palatal impacted canines: a systematic review - Rosanna Guarnieri; Serena Bertoldo; Michele Cassetta; Federica Altieri; Camilla Grenga; Maurizio Vichi; Roberto Di Giorgio; Ersilia Barbato (BMC, 2021)
Abstract Background This review evaluates, as a primary outcome, which surgical technique (open vs. closed) and which type of material used for the auxiliaries (elastic vs. metallic) were preferable in terms of periodontal results during the treatment of palatal-impacted canines. The timing of the evaluation of the results was also assessed as a secondary outcome. Methods An electronic search of the literature up to March 2021 was performed on Pubmed, MEDLINE (via Pubmed), EMBASE (via Ovid), Cochrane Reviews and Cochrane Register of Controlled Trials (RCTs) (CENTRAL). The risk of bias evaluation was performed using version 2 of the Cochrane risk of bias tool (RoB 2) for RCTs and the ACROBAT NRSI tool of Cochrane for non-RCTs. Results 11 articles met the inclusion criteria. Only one RCT was assessed as having a low risk of bias and all the non-RCTs were assessed as having a serious risk of bias. This review revealed better periodontal results for the closed technique and metallic auxiliaries. In addition, it revealed that the timing of the evaluation of the results affects the periodontal results with better results obtained 2 years after the end of treatment. Conclusion In the treatment of a palatal-impacted canine, the closed technique and metallic auxiliaries should be preferred in terms of better periodontal results. The timing of the evaluation of the results affects the periodontal results.